Types of English Teachers’ Questioning and Classroom Interaction Affecting Learners’ Motivation in EFL Context - Nurqadriyanti Hasanuddin; Dyah Setyowati Ciptaningrum (Indonesian Journal of EFL and Linguistics, 2021)
The research aims to reveal the types of teachers’ questioning and classroom interaction that most affecting the EFL learners’ motivation. A mixed-method design was employed in this study with 30 students and a teacher as the respondents. The quantitative and qualitative data were gained through questionnaires and a structured interview for the students, and an observation checklist of the teaching process during three meetings. The data from the questionnaire were analyzed using Descriptive Statistics on SPSS Version 22. Moreover, the analysis of interview data was completed through data condensation, data display, and drawing/verifying conclusions. The observation checklist was used to reveal the kinds of questioning and classroom interaction that is frequently used by the teacher. Based on the quantitative data, it was found that the types of questioning affecting the students’ motivation were the leading, display, and open-ended questions. However, the types of questioning that the most frequently used by the teachers are referential and display questions. Moreover, the questionnaire result showed that the whole classroom and group interaction were the types of classroom interactions that most motivated the students in the learning process. From the observation, the teacher facilitated the student with various classroom interactions based on their need. Overall, the teacher has facilitated the students with the kinds of questioning and classroom interaction that motivates the student in learning.